1983
DOI: 10.1002/bscb.19830920212
|View full text |Cite
|
Sign up to set email alerts
|

Digallic Acid

Abstract: SUMMARYDigallic acid was prepared by partial acid hydrolysis of tannic acid and purified by Counter Current Distribution. In water and methanol solution digallic acid is present in two isomeric equilibrium forms which were named meta and para digallic acid. Meta digallic acid, the main component, is stable in ether and acetone solution. The above was proved by HPLC, GC-MS and NMR experiments on digallic acid and on its permethylation product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The two singlet peaks at 7.07 and 7.25 ppm were not assigned with these F 2 -selective 2D NMR spectra. However, the CT-HMBC spectrum indicated that these peaks may arise from a galloyl group; therefore, these peaks were presumed to arise from p -digallic acid by referring to the former reports. , …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The two singlet peaks at 7.07 and 7.25 ppm were not assigned with these F 2 -selective 2D NMR spectra. However, the CT-HMBC spectrum indicated that these peaks may arise from a galloyl group; therefore, these peaks were presumed to arise from p -digallic acid by referring to the former reports. , …”
Section: Resultsmentioning
confidence: 90%
“…However, the CT-HMBC Journal of Agricultural and Food Chemistry spectrum indicated that these peaks may arise from a galloyl group; therefore, these peaks were presumed to arise from p-digallic acid by referring to the former reports. 29,30 In the F 2 -selective 2D NMR spectra, amine protons were observed with high sensitivity (Figure 2b, 3a). Because amine protons are exchangeable, they are difficult to detect in a deuterated solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Given that the radical scavenging and antioxidant properties of gallic acid are known [ 20 ], the compound was not pursued further. The other two early-eluting peaks were identified as a 7:3-mixture of meta- and para-digallic acid ( 2 ) [ 21 ] and a gallic acid methyl ester ( 3 ) [ 22 ]. Both compounds were found to possess good radical scavenging activity ( Table 2 ), which was in accordance with the well-known radical scavenging properties of gallic acid [ 20 ].…”
Section: Resultsmentioning
confidence: 99%